Study the effect of agar extraction pH on its yield and physical properties from the Syrian marine alga Pterocladia capillacea - Mayhoob, Hamed; Abbas, Assef; Mahmod, Ali (Latakia University Journal -Biological Sciences Series, 2018)
The research aims to study is to study the effect of the pH factor of Pterocladia capillacea on agar yield and some of its physical properties using different degrees of pH (4- 5.5 - 5.5 - 6.5 - 7.5 - 7.5 - 8). The maximum yield of agar was 37.45% at pH = 5 and 562g / cm2 and viscosity 10.7cP and 15.45% at pH = 8 with the highest strength of 768 g /cm2 and viscosity of cP 156. The degree of melting and melting of agar Between (22- 33.5 οC) and (75- 86 οC), respectively. دراسة تأثير درجة pH استخلاص الأغار في مردوده و خواصه الفيزيائية من الطحلب البحري السوري Pterocladia capillacea يهدف البحث إلى دراسة تأثير عامل pH استخلاص الأغار من الطحلب البحري capillacea Pterocladia في مردود الأغار وبعض خصائصه الفيزيائية وذلك باستخدام درجات مختلفة من pH (4- 4.5- 5- 5.5 – 6 – 6.5 – 7- 7.5 - 8). بلغ المردود الأعظمي للأغار المنتج 37.45 % عند درجة pH=5 و قوة تهلم 562g/cm2 ولزوجة 10.7cP وأدنى قيمة 15.45% عند عند درجة pH=8 مترافقة مع أعلى قوة تهلم 768 g/cm2 ولزوجة cP 156. تراوحت درجة تهلم و ذوبان الأغار بين ( 22و 33.5 C٥) ثم ( 75و 86 C٥) على التوالي.